Model Experiential Learning pada Pembelajaran IPA: Systematic Literature Review - Esti Susiloningsih; Mohamad Syarif Sumantri; Arita Marini (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine and describe the effect of the experiential learning model on science learning in elementary schools, namely by looking at the achievement of science learning objectives. The method used in this study is the Systematic Literature Review method. The search results found 244 articles from 2011 to 2023, and then were gradually and systematically selected into 15 articles that were relevant to the topic of experiential learning models in elementary school learning science and true/matching criteria. The results of this study indicate that there is an influence of the experiential learning model on science learning in elementary schools, as evidenced by the 15 articles studied being able to answer research questions, namely: How is the achievement of science learning objectives in elementary schools based on the results of a review of research articles on the experiential learning model?, and Does experiential learning affect the achievement of the goals of learning science in elementary schools? The results and findings in these articles indicate an increase in the achievement of science learning objectives after the implementation of this experiential learning model, namely: increasing students' curiosity and learning achievement, increasing students' motivation, Increasing students' understanding of students, improving the quality of learning, increasing the competence of students, and making learning fun.